2020
DOI: 10.1186/s12889-020-09457-z
|View full text |Cite
|
Sign up to set email alerts
|

Towards achieving the 90–90–90 HIV targets: results from the south African 2017 national HIV survey

Abstract: Background Measuring progress towards the Joint United Nations Programme on HIV/AIDS (UNAIDS) 90–90–90 treatment targets is key to assessing progress towards turning the HIV epidemic tide. In 2017, the UNAIDS model estimated that 75% of people living with HIV (PLHIV) globally knew their HIV positive status, 79% of those who knew their status were on antiretroviral therapy (ART), and 81% of those who knew their HIV status and were on ART had a suppressed viral load. The fifth South African natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 23 publications
5
94
0
Order By: Relevance
“…The preventive benefits of antiretroviral therapy (ART) are well established [ 1 ], but challenges remain with HIV care uptake. Recent national data from South Africa indicate that only 52% of people living with HIV (PLHIV) aged 15 or older are virally suppressed [ 2 ]. This comes despite improved medication access through policies for Universal Test & Treat (UTT), Same‐Day Initiation (SDI) of ART [ 3 ] and decentralized medication initiation and monitoring [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preventive benefits of antiretroviral therapy (ART) are well established [ 1 ], but challenges remain with HIV care uptake. Recent national data from South Africa indicate that only 52% of people living with HIV (PLHIV) aged 15 or older are virally suppressed [ 2 ]. This comes despite improved medication access through policies for Universal Test & Treat (UTT), Same‐Day Initiation (SDI) of ART [ 3 ] and decentralized medication initiation and monitoring [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa has a high prevalence of diseases such as diabetes (12.8%), hypertention (41.6 -54%), and obesity (68% of females, 31% of males) (13). In 2017, a national survey of HIV prevalence showed that about 14.6% of the South African population was living with HIV (14), additionally 11-12% of HCWs in South Africa are HIV infected (15). The prevalence of tubercolosis (TB) in South Africa was 3.6% (16), in addition high rates of TB infections have been recorded among South African HCWs, with an active TB disease incidence of 1.13% to 1.47% (15,17).…”
mentioning
confidence: 99%
“…Of these 7 million HIV-infected patients, only 70.7% (~5.3 million) of patients are currently receiving combined antiretroviral therapy (ART). 1 …”
Section: Contextmentioning
confidence: 99%